Digital transformation and digital literacy in the context of complexity within higher education institutions: a systematic literature review - Silvia Farias-Gaytan; Ignacio Aguaded; Maria-Soledad Ramirez-Montoya (Humanities & Social Sciences Communications, 2023)
Abstract The incessant changes in technology generate new products and services, presenting multiple opportunities for the complex educational environment. Consequently, higher education institutions must be attentive to these changes to ensure that students have the knowledge and skills necessary for the work environment. This research aimed to identify studies related to digital transformation and digital literacy in higher education institutions through a systematic study of literature. The search resulted in 830 articles published in the Scopus and Web of Science databases from 2015 to 2022. Quality questions, inclusion and exclusion criteria were applied where 202 articles were selected for the study. The results show (a) interest of educational institutions in empirical studies where technologies are incorporated for didactic purposes, (b) challenges of opportunity in training programs to develop digital competences of teachers and students, (c) little interest in the development of media literacy, (d) the methodological aspects of the studies allow exploring new perspectives of digital transformation in higher education. This article may be of interest to academics, decision-makers and trainers of future professionals to introduce educational technology into learning processes in line with the complex demands of the world of work and society.